Progress and prospects in the management of bacterial infections and developments in Phytotherapeutic modalities. (15th March 2020) - Akram, Muhammad; Riaz, Muhammad; Munir, Naveed; Rasul, Akhtar; Daniyal, Muhammad; Ali Shah, Syed Muhammad; Shariati, Mohammad Ali; Shaheen, Ghazala; Akhtar, Naheed; Parveen, Farzana; Akhter, Naheed; Owais Ghauri, Aymen; et al.
Abstract: The advent of antibiotics revolutionized medical care resulting in significantly reduced mortality and morbidity caused by infectious diseases. However, excessive use of antibiotics has led to the development of antibiotic resistance and indeed, the incidence of multidrug‐resistant pathogens is considered as a major disadvantage in medication strategy, which has led the scholar's attention towards innovative antibiotic sources in recent years. Medicinal plants contain a variety of secondary metabolites with a wide range of therapeutic potential against the resistant microbes. Therefore, the aim of this review is to explore the antibacterial potential of traditional herbal medicine against bacterial infections. More than 200 published research articles reporting the therapeutic potential of medicinal plants against drug‐resistant microbial infections were searched using different databases such as Google Scholar, Science Direct, PubMed and the Directory of Open Access Journals (DOAJ), etc., with various keywords like medicinal plants having antibacterial activities, antimicrobial potentials, phytotherapy of bacterial infection, etc. Articles were selected related to the efficacious herbs easily available to local populations addressing common pathogens. Various plants such as Artocarpus communis, Rheum emodi, Gentiana lutea L., Cassia fistula L., Rosemarinus officinalis, Argemone maxicana L, Hydrastis canadensis, Citrus aurantifolia, Cymbopogon citrates, Carica papaya, Euphorbia hirta, etc, were found to have significant antibacterial activities. Although herbal preparations have promising potential in the treatment of multidrug‐resistant bacterial infection, still more research is required to isolate phytoconstituents, their mechanism of action as well as to find their impacts on the human body.